Family Involvement, Governmental Connections, and IPO Underpricing of SMEs in China. (June 2020) - Yang, Jie; Ma, Jieqiong; Doty, D. Harold
This study draws on institutional theory to explore the relationship between family involvement, governmental connections, and initial public offering (IPO) underpricing in China. We explore these relationships using a sample of 577 manufacturing firms listed on the small and medium enterprises board of the Shenzhen Stock Exchange over a 10-year period (2004-2014). In contrast with previous literature, we found that Chinese family firms tend to exhibit less IPO underpricing than nonfamily firms. In addition, we found family members' political ties enhance the negative relationship between family involvement and IPO underpricing. In contrast, state ownership mitigates the above relationship.